1969
DOI: 10.1128/aem.18.4.677-679.1969
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Antibiotic Sensitivities of Ruminal Bacteria1

Abstract: Fifteen species of ruminal bacteria were tested against 10 antibiotics in concentrations ranging from 0.1 to 200 /ig/ml in an anaerobic tube dilution system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The basic mode of action of ionophore compounds is on transmembrane ion fluxes and the dissipation of cation and proton gradients, thereby interfering primarily with transport systems and ATP synthesis (3). Susceptibility and resistance patterns of ruminal bacteria to avoparcin and tylosin are in agreement with previous reports (1,15,36,38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The basic mode of action of ionophore compounds is on transmembrane ion fluxes and the dissipation of cation and proton gradients, thereby interfering primarily with transport systems and ATP synthesis (3). Susceptibility and resistance patterns of ruminal bacteria to avoparcin and tylosin are in agreement with previous reports (1,15,36,38).…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al (38) reported that Streptococcus bovis is susceptible to tylosin only at high concentration (MIC -100 ,ug/ml). Walton (37) noted that avoparcin was not inhibitory to some gram-positive enteric streptococci, and Dutta and DeVriese (12) have reported a number of lactobacilli against which avoparcin had no activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal fermentation changes induced by some of the antimicrobial compounds have been shown to be similar to those induced by monensin and lasalocid in that the acetate:propionate ratio is decreased, lactic acid production is inhibited, methanogenesis is depressed and ruminal degradation of protein and amino acids is lowered (Dyer et al, 1980;Muir et al, 1980;Froetschel et al, 1983;Demeyer and VanNevel, 1985;Merchen and Berger, 1985;Nagaraja et al, 1985). Also, sensitivity and resistance of ruminal bacteria to the various antimicrobial compounds used in the present study were very similar to their responses to lasalocid and monensin; gram-positive bacteria were resistant and gram-negative bacteria were sensitive (Akkad and Hobson, 1966;Wang et al, 1966;Fulghum et al, 1968;Watanabe et al, 1981;Stewart et al, 1983;Nagaraja and Taylor, 1987). Avoparcin and tylosin have been shown to be less inhibitory to the two major gram-positive lactic acid-producing bacteria (Streptococcus bovis and Lactobacillus; Walton, 1978;Dutta and DeVriese, 1981;Nagaraja and Taylor, 1987).…”
Section: Effects Of Antimicrobial Compounds On Lactic Acid Productionsupporting
confidence: 68%
“…Nagaraja and Taylor (16) showed that M. elsdenii was totally resistant to eight antimicrobial feed additives. The susceptibility and resistance of M. elsdenii to 13 other antibiotics were reported by El Akkad and Hobson (3) and Wang et al (23). Each study examined one strain only.…”
Section: Discussionmentioning
confidence: 87%